Computing covariance matrices for constrained nonlinear large scale parameter estimation problems using Krylov subspace methods - Kostina, Ekaterina; Kostjukova, Ol'ga I. (Constrained Optimization and Optimal Control for Partial Differential Equations, 2012)
In the paper we show how, based on the preconditioned Krylov subspace methods, to compute the covariance matrix of parameter estimates, which is crucial for efficient methods of optimum experimental design.